THE IMPLEMENTATION OF PODCAST IN TEACHING LISTENING SKILLS TO SENIOR HIGH SCHOOL ENGLISH CLUB STUDENTS - Rahmat, Hepi Janwaristia; Suprijadi, Dasep; Melian, Osi Havis (IKIP Siliwangi, 2024)
The increasing sophistication of life, particularly in academic and educational fields, has led to the evolution of digital recording media, such as podcasts. Podcasts offer various topics and channels, making them suitable for learning and developing students' listening skills. This research aimed to portray podcast implementation as a learning tool for English club students, using a qualitative method to collect data. This research was administered to 15 students of an English club at a senior high school. This research used qualitative methods. The instrument employed in this research was observation with field notes. The study describes the process of podcast integration in teaching listening skills to English club students through three stages covering: pre-activity, whilst-activity, and post-activity. The pre-activity showed the teacher introducing the material and providing trigger questions at the beginning regarding listening skills using a podcast medium. The students were active in responding, answering, and asking questions. In the whilst-activity, the teacher implemented a podcast to clarify the speaker's message and help students understand the material. Then, she provided directions when carrying out the lesson; students were given directions to understand what the speakers said and write down important points from the podcast. In the Post-activity, students can present the main points of podcast material dealing with ‘the right way to say sorry.’ Then, students and teachers carry out a reflection activity and conclude from what they have learned.